No longer a girl: my female experience in the masculine field of martial arts - Martínez, Alejandra (2015)
This autoethnographic paper arises from my interest in studying contemporary masculinities in the city of Cordoba, Argentina. It describes my experience as a female in the masculine space of a karate dojo and is based on records from a martial arts class between 2005 and 2010. I have selected some of the moments that I consider the most significant in order to convey three elements: a) life in the dojo, including rituals and specific practices, b) the exaltation of masculinity and the trials that men must overcome, and c) the experience of masculinity in my own body as a woman who enters a man?s world and strives to be a part of it.